DIGITALIZATION, DUAL-USE TECHNOLOGIES AND MANAGEMENT OF NEW BUSINESS MODELS - WAYS TO RESPOND TO CHALLENGES. USH PROBUSINESS, WALACHIA HUB AND DUAL-USE CLUSTER STUDY CASE - LIANU, Costin; RADULESCU, IRINA GABRIELA; LIANU, COSMIN (Annals of Spiru Haret University. Economic Series, 2020)
Dual use technologies, which means technologies used for both military and civil applications, are evolving in the context of digitalization. Even in pre-digital era, at the dawns of the technological progress of mankind, the use of technologies was ambivalent, both for warfare and civil wellbeing. Now however, we assist to a fast blending of dual use and digital processes which is changing the landscape of the business models. We name this new process interaction as Dual-use Digital Blending (DDB). This paper is investigating the trends of evolution of this blended dual use-digital transformation technologies and their impact on the new geo-economic and geopolitical confrontations, on the trade flows and economic balance of power. We look at the new emerging business models triggered by the DDB and the managerial challenges this will require especially for innovative start-ups and SMEs. Finally, we argue that university led innovation ecosystem, like the study case presented, may offer knowledge hubs for managers, organized in clusters in order to be better prepared for the described DDB process.